Presence of Candida pelliculosa and Enterobacter cloacae in Street Food of Mumbai - Shah, Pratibha J; Khanvilkar, Salooni; Mehta, Hanisha; Yadav, Priyanka (International Journal of Scientific Research in Biological Sciences, 2023)
India is a densely populated country and is popular for its street-food. Food–borne infections are a well-recognized problem worldwide. The aim of this study was to evaluate the microbial load and safety issues of randomly obtained street-food samples sold in the streets of Mumbai. The food samples were analysed for their viable count, identification and antibiogram pattern of the isolates were also carried out. The average total viable count of all analysed food samples was found to be 2.19 x 104 cfu/ml. In this study, presence of Candida pelliculosa and Enterobacter cloacae are being reported for the first time in Mumbai`s street-food. Both Candida pelliculosa and Enterobacter cloacae have been reported in neonatal intensive care units of hospitals. Antibiotic and antifungal susceptibility tests of the isolates were carried out and Candida pelliculosa was found to be resistant to antifungals-Polymyxin B, Colistin, Clotrimazole, and Fluconazole. Enterobacter cloacae was found to be susceptible to Ciprofloxacin, Cefotaxime, Tetracycline and Imipenem and was resistant to Vancomycin and Erythromycin. As the worldwide urban population increases with rapid migration from rural areas, street-vended foods play a key role but also pose food safety challenges when they are prepared with disorganised food safety guidelines in small and unauthorised eateries. The vendor practices and hygiene of the vending area may be the reason for finding high microbial load in food samples. Hence the study emphasizes on the need to regulate the unauthorised and small food selling outlets, by conducting trainings, developing infrastructure, and carrying out regular inspections in a densely populated place like Mumbai.